The Art of Intramedullary Nailing for Femoral Fracture - Yang, Kyu Hyun.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book offers precise points in intramedullary nailing for the treatment of the femoral fracture. The author's aim is to explain how to find a correct entry point, especially in the case of subtrochanteric fracture with excessive external rotation of the proximal fragment, method of reduction in a severely comminuted fracture which is challenging in the restoration of rotational alignment as well as angulation, and mode of interlocking. This book is based on the author$1 (Bs personal experiences of 30 years in trauma, who dedicates himself to developing intramedullary nailing for femoral shaft fracture. It also covers cephalomedullary nailing for reverse obliquity trochanteric fracture because the incidence of hip fractures increases due to prolonged life expectancy. This book will be an ideal resource with many fluoroscopic and radiographic pictures to descript the real situations that the surgeons encounter in the operating room and techniques to solve those problems. .s
1. History of IM nailing -- 2. Prerequisites for femoral nailing -- 3. Analysis of fracture configuration and entry point -- 4. Reduction technique -- 5. Mode of fixation -- 6. Postop. Rehabilitation -- 7. Trochanteric fracture -- 8. Analysis of fracture configuration -- 9. Stable reduction -- 10. Ideal implant for unstable fracture.
Keywords: Orthopedics; Orthopedic surgery; Surgery; Orthopaedics; Surgical Orthopedics; Surgery; Fracture Fixation, Intramedullary